Hybrid state systems: As a new system modeling tool for future - (:unkn) unknown (INT INST INFORMATICS & SYSTEMICS, 1998)
Hybrid state systems (HSS) are modeled as a combination of Discrete State (DSS) and Continuous State Systems (CSS). The continuous state space can be divided into regions so that in every region depending on the discrete state of HSS the continuous state system dynamic functions are found. Three examples of engineering systems from different areas are modeled and studied as hybrid state systems.
Keywords: modeling; systems; hybrid systems; Discrete and Continuous State Space